Investigation of the influence of chatter on tool wear - Amin, A. K. M. Nurul; N. V., Talantov (1987)
Experimental investigations have been carried out to determine the influence of chatter on cemented carbide tool wear in turning medium carbon steel. Conditions of stable cutting and those conducive to intensive chatter in the investigated range of cutting speed and other cutting conditions were established. Tool wear test performed under these two different conditions have facilitated to establish the typical nature of tool wear during chatter. Chatter leads to intensive wear of the flank surface due to additional rubbing of the same along the wavy cutting surface, formed during chatter. Besides chatter leads to lowering down of the values of chip-tool contact lengths due to a lower value of the coefficient of chip shrinkage. Consequently tool wear along the rake surface is less during chatter.